Spontaneous Emission Induced Entanglement and Steady Entanglement in Two Atomic System (Journal of Atomic and Molecular Sciences, 2016)
We report possibility of generating entanglement between two atoms in freespace when their spatial separation is on the order of wavelength or less. We show thatthese two atoms get coupled by photon exchange due to spontaneous decay, which inturn generates the atomic entanglement. By introducing the incoherent pumping, onecan obtain the steady entanglement, and the incoherent pumping can overcome thedecay of the atoms. Moreover, one can obtain the larger value of steady entanglementvia proper tuning the incoherent pumping.
Keywords: Quantum Entanglement; Spontaneous Emission; Photon Exchange.